Penggunaan Media Papan Sebab Akibat untuk Meningkatkan Literasi Baca Tulis Kelas 5 SDN Panggung Lor - Mirawati, Diah; Nuvitalia, Duwi; Saputra , Henry Januar; Prasetiawati, Catur (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This study aims to determine the improvement of reading and writing literacy of 5th grade students of SDN Panggung Lor Semarang by applying the cause and effect board learning media. Using a descriptive quantitative method of one-group Pretest Posttest with a research population of 28 students. There are 16 female students and 12 male students. This study uses data collection techniques in the form of pretest and posttest sheets and observations during learning activities. In the initial condition, students were lazy to read during learning activities, causing low literacy, then by applying the learning media of the cause and effect board in Indonesian language learning activities, students became enthusiastic so that their learning scores increased. This was obtained through a paired sample t test of .000 <0.05, which means that there is a difference in the average value of students before and after using the cause and effect board media in learning. The pretest score has an average of 56.43 and the posttest has an average increase to 78.57. From these results it can be concluded that there is an increase in students' literacy through their learning outcomes by applying the cause and effect board learning media.